The Conflict between the Objectives of Restorative Justice and its Implementation in Marriage Cases of Rape Victims and Perpetrators in Indonesia - Permata, Karina; Azahra, Serla Yolanda; Hosnah, Asmak Ul (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to examine the conflict between the goals of restorative justice and its implementation in marriage cases involving rape victims and perpetrators in Indonesia. Using a desk-based research method, this study analyzes legal frameworks, case studies, and relevant literature to understand the dynamics of restorative justice in this context. The results show that many sexual violence cases are inadequately resolved, with a significant percentage of victims not receiving satisfactory outcomes, often leading to forced marriages or financial compensation instead of justice. This research concludes that restorative justice practices should not be applied to rape cases and law enforcement officials must understand the concept and purpose of restorative justice in implementing it. Law enforcement in rape cases should prioritize recovery and justice for victims.